Climate change, rice production, and migration in Vietnamese households - Adelaide Baronchelli; Roberto Ricciuti (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper analyses the relationship between climate and migration in rural households in Viet Nam. We propose an instrumental variable approach that controls for the potential endogeneity between crop production and migration using monthly minimum temperatures in the growing season as an instrument of rice production. Results show that the rise in minimum temperature during the core month of the growing season (i.e. June) does cause a reduction in rice production which, in turn, has a positive impact on people's propensity to migrate. This finding is robust to the use of different estimators and plausible violations to exogeneity of the instrument.
Keywords: O15; R23; Q12; Q54; 330; climate change; rice production; migration; Viet Nam